A unified model of relative deprivation and risk-laden migration - Oded Stark (Global Labour in Distress, Volume I, 2022)
Received migration research has it that higher relative deprivation strengthens the incentive for people to migrate, and that often migration is a risky enterprise. Relative deprivation has been seen as a push factor in migration, and the level of risk involved in migration has been understood to reduce its attraction. Here we reveal a positive relationship between the level of relative deprivation experienced at origin and willingness to undertake risk-laden migration: we show that higher relative deprivation is matched by riskier acceptable migration options. In expanding the range of acceptable risk-laden migration options, relative deprivation experienced at origin acts also as a migration pull factor.
Keywords: 330